2015
DOI: 10.1109/tns.2015.2391197
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Performance of CsI(Tl) Scintillation Films With Pixel-Like Columnar-Matrix Structure

Abstract: In the recent decade, pixelated CsI(Tl) scintillation films are developed for X-ray imaging to improve spatial resolution. Several methods have been reported but better performance is still required. In this work, CsI(Tl) films were prepared on specially designed patterned substrates with regular arrays of pits. Each CsI(Tl) micro-column locates in one pit. In this way, CsI(Tl) films with pixel-like columnar-matrix structure were achieved. Each pixel contains one micro-column and the size of pixel is the avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Compared to the densely packed pixel‐like columnar CsI:Tl, the matrix route currently suffers from a low loading ratio of scintillators, similar to the polymer matrix route, which leads to a compromised light output and hence impairs sensitivity and spatial resolution. To date, the columnar structured film, as exemplified by CsI:Tl grown via a patterned template‐assisted thermal evaporation process, [ 40 ] remains the most promising strategy and is worthy of exploration for recently emerged metal halides. Moreover, it would be exciting if metal halide array fabrication could embrace the innovative micromachine technologies recently tailored for metal halides, such as ion‐exchange lithography, [ 85 ] photocatalysis‐initiated lithography, [ 86 ] and ultrafast laser lithography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the densely packed pixel‐like columnar CsI:Tl, the matrix route currently suffers from a low loading ratio of scintillators, similar to the polymer matrix route, which leads to a compromised light output and hence impairs sensitivity and spatial resolution. To date, the columnar structured film, as exemplified by CsI:Tl grown via a patterned template‐assisted thermal evaporation process, [ 40 ] remains the most promising strategy and is worthy of exploration for recently emerged metal halides. Moreover, it would be exciting if metal halide array fabrication could embrace the innovative micromachine technologies recently tailored for metal halides, such as ion‐exchange lithography, [ 85 ] photocatalysis‐initiated lithography, [ 86 ] and ultrafast laser lithography.…”
Section: Discussionmentioning
confidence: 99%
“…reported a series of pixel‐like columnar CsI:Tl arrays with finely adjusted column size. [ 40 ] It was shown that with the column size decreases from 8 to 3 µm, the spatial resolution of the 50 µm thick scintillator was increased from 7.6 to 14 lp mm −1 , indicating the crucial role of pixel size in the design of array scintillators. ii) Phase‐separated array scintillators prepared from binary eutectic.…”
Section: Material‐form‐associated Light Propagation In Metal Halide S...mentioning
confidence: 99%
“…To improve imaging resolution further, Yao and co‐workers modified the template and fabricated a structured scintillator with finer array. [ 92 ] An array with a period of 3 µm was patterned on the template surface, and a spatial resolution of approximately 18 lp mm ‐1 at a MTF of 10% could be obtained with the optimized sample.…”
Section: Array‐derived Structured Scintillatorsmentioning
confidence: 99%
“…However, increasing the thickness of the scintillation screens often comes at the expense of their spatial resolution because of the lateral spreading of scintillation light 4 . To overcome this limitation, CsI(Tl) scintillation screens with a needle-like columnar structure were developed through a thermal evaporation method 5 . The vertical columnar structure can suppress the lateral spreading of scintillation light and preserve the spatial resolution of X-ray imaging.…”
Section: Introductionmentioning
confidence: 99%